Investment Commitments in Sub-Saharan Africa Stayed at a Peak Level in 2007 - Izaguirre, Ada Karina; Perard, Edouard (World Bank, Washington, DC, 2012)
Investment commitments to infrastructure projects with private participation in Sub-Saharan Africa amounted to almost US$11 billion in 2007, the second highest level since 1990, according to just-released data from the private participation in infrastructure project database. The region accounted for 7 percent of the year's total investment commitments in developing countries. Investment commitments in 2007 were down 10 percent from the level in 2006, the highest in 1990-2007. The regional peak in that year, however, was driven in part by an unusually large project: the US$3.4 billion Gautrain light rail project in South Africa, which had government cash support of around US$3 billion. If that project were excluded, investment in 2007 would be the highest ever in the region. Investment in 2007 was driven mostly by projects implemented in previous years. Projects reaching financial closure in 1990-2006 attracted US$7.6 billion, while the 24 new projects implemented in 2007 accounted for US$3.3 billion. Investment in physical assets declined by 22 percent to US$8.5 billion, still the second highest level ever. Payments to governments almost doubled to reach a peak level of US$2.5 billion, about 23 percent of annual investment.